Benefits of implementing a telemetry system for mining operations management - Felsch Junior, Walter Schmidt (2018)
This research presents the benefits of using telemetry in the operations management of a high-production open-pit mine located in the state of Minas Gerais, Brazil. Caterpillar’s telemetry systems called Vital Information Monitoring System (VIMS) were used to monitor trucks via input device signals (sensors and switches), providing action alert messages for the operator through a visor in the cockpit. The processes that will be subject to control are: fuel supply, load imbalance, access conditions, and temperature of the brake cooling system. An interface was developed with the IntelliMine (Modular Mining Systems) fleet management system for mining operations management. A system that identifies the type of problem was implemented, as well as the most efficient means for its resolution and localization in real time.